The Immunometabolism Respiratory Infections: Disintegration of Microbial-Immune-Metabolism Crosstalk Regulates Disease Progression - Suzan Radhi Hussein; Zahraa Abdalameer; Sara Abdulkhaliq Mahdi Abdulkarem Alfatlawi (African Journal of Advanced Pure and Applied Sciences, 2026)
Respiratory infections caused by influenza, respiratory syncytial virus (RSV), transmission of the viruses that cause the current pandemic and transmission of the bacteria Mycobacterium tuberculosis, represent a major health burden globally. Beyond direct pathogen--host interactions, there is mounting evidence that the metabolic programming of immune and structural lung cells--immunometabolism--critically affects outcome of infection. Pathogens then take over or alter metabolic pathways to their advantage for replication and immune cells then rewire metabolism to their advantage against infection, a dynamic metabolic battlefield. This review summarizes the latest progress in immunometabolism from respiratory infections in terms of metabolic-immune-microbial crosstalk, severity of disease, and novel host-directed therapeutic targets. Pathogenic: Across pathogens, infection triggers glycolytic rewiring, tricarboxylic acid (TCA) cycle remodelling, deregulation of lipid and amino acid metabolism metabolic hubs (itaconate/IRG1, succinate/HIF-1a and NAD+/sirtuin axes) are linked to the metabolic flux, cytokine production, ROS signalling and tissue injury. Human metabolomic research presents disease severity fingerprints including lactate, succinate, kynurenine and ceramide pathways. Therapeutically, metabolic interventions (glycolysis inhibitors, itaconate derivatives, NAD+ boosters) hold promise in preclinical models, although only limited clinical translation has been made. Immunometabolic reprogramming: Immunometabolic reprogramming is a determinate of respiratory infection pathogenesis and resolution. Targeting metabolic checkpoints could be a new field for host-directed therapy for emerging treatments, but requires context-specific approaches, combination of spatial-multi-omics, endotyping metabolomics in clinical trials.